Implementasi Administrasi Keuangan dalam Meningkatkan Ketertiban Pencatatan Transaksi pada PT. Sinturi Multi Usaha - Evelyn; Budi Harsono (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2026)
The Campus Impact Program through Independent Internships is a learning initiative that provides students with the opportunity to gain hands-on work experience. This internship was conducted at PT. Sinturi Multi Usaha, a company engaged in the wholesale trade of motor vehicle parts and accessories. The objective of this activity was to support improvements in the company’s financial administration while enhancing students’ competencies in accounting and finance. The methods used included observation, interviews, documentation, direct participation in operational activities, transaction document verification, and recording transactions using the GF-Accounting system. The results indicate that the company’s financial administration functions effectively through document verification procedures, structured transaction recording, and the use of a computerized accounting system.